Comparison of Outpatient Mechanical Cervical Ripening Methods to Standard Inpatient Ripening - Goering, Mary P.; Wunderlich, Whitney L.; Vacquier, Marc C.; Watson, David A.; Drake, Kelly A.; Hoffman, Sandra I.; Schulte, Anna; Colicchia, Laura C.; Sidebottom, Abbey C. (American Journal of Perinatology, 2025)
This study aimed to assess clinical efficiency and maternal and neonatal outcomes for patients who underwent outpatient cervical ripening using mechanical methods (osmotic dilators and Foley balloon) compared with patients who underwent inpatient ripening.A retrospective cohort study from March 2020 to March 2022 compared patients with low-risk, term, singleton pregnancies who underwent outpatient cervical ripening to clinically similar patients who had inpatient ripening. Inverse probability of treatment weighting for analysis of outcomes to account for differences in groups and comparisons of outcomes are reported as mean differences with 95% confidence intervals (CIs).The cohort included 391 patients (116 outpatient, 275 inpatient). Among the outpatient group, half used only mechanical devices, and all others received additional pharmacological methods after admission for labor induction. Among the inpatient group, the most common cervical ripening method was pharmacological only (66.2%), followed by both pharmacological and mechanical (25.8%), and 8% used only mechanical. After outpatient cervical ripening, patients had significantly higher cervical dilation (mean difference 1.9 cm, 95% CI: 1.6, 2.3) and simplified bishop scores (mean difference 1.6, 95% CI: 1.2, 2.1) on admission compared with the inpatient group. The average time from admission to delivery was 5.8 hours shorter (95% CI: −8.6, −2.9) for the outpatient group compared with the inpatient group, and the average total length of stay was 7.1 hours shorter (95% CI: −12.1, −2.1) for the outpatients among patients with vaginal deliveries. Both groups had similar hours of oxytocin use, and mode of delivery, and did not differ for maternal complications or neonatal outcomes.Outpatient cervical ripening using multiple mechanical methods was associated with significantly higher cervical dilation, shorter average time from patient admission to delivery, and shorter total length of stay for vaginal deliveries. Outpatient cervical ripening may be an important option for easing resource utilization for induced labor.
Keywords: cervical ripening; induction; Foley balloon; osmotic dilator; outpatient; Dilapan-S